Advances in Reasoning-Based Image Processing Intelligent Systems Conventional and Intelligent Paradigms - Kountchev, Roumen; Nakamatsu, Kazumi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The book puts special stress on the contemporary techniques for reasoning-based image processing and analysis: learning based image representation and advanced video coding; intelligent image processing and analysis in medical vision systems; similarity learning models for image reconstruction; visual perception for mobile robot motion control, simulation of human brain activity in the analysis of video sequences; shape-based invariant features extraction; essential of paraconsistent neural networks, creativity and intelligent representation in computational systems. The book comprises 14 chapters. Each chapter is a small monograph, representing resent investigations of authors in the area. The topics of the chapters cover wide scientific and application areas and complement each-other very well. The chapters$1 (Bcontent is based on fundamental theoretical presentations, followed by experimental results and comparison with similar techniques. The size of the chapters is well-ballanced which permits a thorough presentation of the investigated problems. The authors are from universities and R&D institutions all over the world; some of the chapters are prepared by international teams. The book will be of use for university and PhD students, researchers and software developers working in the area of digital image and video processing and analysis.s
From the content: Performance analysis and comparison of the Dirac video codec with H.264/ MPEG-4, Part 10 -- Linear and non-linear inverse pyramidal image representation: algorithms and applications -- Preserving data integrity of encoded medical images: the LAR compression framework -- Image Processing in medicine -- Attention in Image Sequences: Biology, Computational Models, and Applications.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).